Legal Protection of Ownership of Hospital Land Rights Following the Issuance of Regulation of the Minister of Health of the Republic of Indonesia Number 56 of 2014 Concerning Classification and Licensing of Hospitals - Susiawanto, Djarot Egro (Jurnal Konstatering, 2024)
The problem of hospital land ownership status began when the Minister of Health Regulation Number 56 of 2014 was issued, based on article 1 of PERMENKES Number 56 of 2014, namely "Hospital Establishment Permit, hereinafter referred to as Establishment Permit, is a permit granted by an authorized official to a Government agency, Regional Government or private bodies that will construct buildings or change the function of existing buildings to become hospitals after fulfilling the requirements stipulated in the Ministerial Regulation. This makes the author interested in researching the legal protection of ownership of hospital land after the publication of Regulation of the Minister of Health of the Republic of Indonesia Number 56 of 2014 concerning Hospital Classification and Licensing. The author conducted this research using a doctrinal type of research with a normative juridical method which was carried out by means of inventory of positive law, efforts to discover the principles and philosophical basis (dogma or doctrine) of positive law. qualitative data analysis. The Minister of Health's regulations governing the Classification and Licensing of Hospitals have undergone several changes. Regarding the licensing requirements for the establishment and extension of hospital operational permits which specifically regulate the status of hospital land ownership, they are only found in Minister of Health Regulation Number 56 of 2014 concerning Classification and Licensing of Hospitals, whereas with the latest Minister of Health Regulation concerning Classification and Licensing of Houses If you are sick in the Transitional Provisions, Minister of Health Regulation Number 56 of 2014 concerning Classification and Licensing of Hospitals is no longer valid. This has resulted in uncertainty regarding the provisions on the ownership status of the hospital's land and has become a polemic in the hospital. Meanwhile, in its implementation of visitation and verification functions, regarding the land ownership status of the Karanggede Sisma Medika Boyolali Hospital, the Boyolali Health Service is still guided by Minister of Health Regulation Number 56 of 2014 concerning Hospital Classification and Licensing, while this regulation has been declared no longer valid. From the description The impact of the uncertainty in regulations regarding licensing requirements for the establishment and extension of hospital operational permits, specifically regarding the ownership status of hospital land, can be concluded that there is no legal protection for hospitals or the public who use hospital services.